Aromaterapi Bunga Lavender Memperbaiki Kualitas Tidur pada Lansia - Kurnia, Anggraini Dwi; Wardhani, Viera; Rusca, Kuswantoro Tri (Fakultas Kedokteran Universitas Brawijaya, 2009)
Sleep is a basic human need, characterized by minimal physical activity, change in physiological process ofthe body and decrease respon from external stimulus. Most of the elderly have high risk to suffer sleepproblem because of some factors. Aromatherapy is a therapy using essential oil which produces comfortableeffect, more steady emotion and feeling, calmer thought and feeling. This research was aimed to identify theeffectivity of Lavender (Lavendula L) Aromatherapy in improving quality of sleep of the elderly in Panti WerdhaMalang. A quasi experiment study was implemented with randomized control group pretest posttest using 18subjects divided into two groups.and treatment. The sleep quality was measured by interview developedbased on PSQI (Pittsburgh Sleep Quality Index). The data were then analyzed using Wilcoxon test and Mann-Whitney test. A significant improvement of sleep quality score was identified in treatment group (3,89, p=0,07) but not in the control group (0,78;p=0,317). These improvement is significantly different between the twogroups (p=.0,001). It can be concluded that Lavender aromatherapy is significantly improve the quality ofsleep in elderly people